Island mammal extinctions are determined by interactive effects of life history, island biogeography and mesopredator suppression. Issue 4 (11th August 2013) - Hanna, Emily; Cardillo, Marcel
Abstract: Aim: Understanding extinction on islands is critical for biodiversity conservation. Introduced predators are a major cause of island extinctions, but there have been few large‐scale studies of the complexity of the effects of predators on island faunas, or how predation interacts with other factors. Using a large database of island mammal populations, we describe and explain patterns of island mammal extinctions as a function of introduced predators, life history and geography. Location: Three hundred and twenty‐three Australian islands. Methods: We built a database of 934 island mammal populations, extinct and extant, including life history and ecology, island geography and the presence of introduced predators. To test predictors of extinction probability, we used generalized linear mixed models to control partially for phylogenetic non‐independence, and decision trees to more fully explore interactive effects. Results: The decision trees identified large mammals (> 2.7 kg) as having higher extinction probabilities than small species (< 2.7 kg). In large species, extinction patterns are consistent with island biogeography theory, with distance from the mainland being the primary predictor of extinction. For small species, the presence of introduced black rats is the primary predictor of extinction. As predicted by mesopredator suppression theory, extinction probabilities are lower on islands with both black rats and a larger introduced predator (cats, foxes or dingoes), compared with islands with rats but no larger predator. Similarly, extinction probabilities are lower on islands with both a mid‐sized (cats or foxes) and a larger (dingoes) predator, compared with islands with cats or foxes only. Main conclusions: Island mammal extinctions result from complex interactions of introduced predators, island geography and prey biology. One conservation implication of our results is that eradication of introduced apex predators (cats, foxes or dingoes) from islands could precipitate the expansion of black rat populations, potentially leading to extinction of native mammal species whose remaining populations are confined to islands.